DISTRIBUSI SPASIAL DAN TIPOLOGI SUMUR KUNA DI DATARAN ALUVIAL PRAMBANAN: Distribusi Spasial dan Tipologi Sumur Kuno di Dataran Aluvial Prambanan - Putri, Anindya Puspita; Yuwono, J. Susetyo Edy; Pratama, Henki Riko (Berkala Arkeologi, 2024)
The cultural potential of the classical period (Ancient Mataram) in the Yogyakarta and Central Java regions can be seen from the dense distribution of existing temples. Apart from the temple, there is data on ancient wells in situ as a marker of the existence of classical period settlements in the Prambanan Alluvial Plain area. The ancient wells found have quite high variations, so they require classification using a scoring method (weighting and grading). The typology of ancient wells are determined by using the criteria of strong and weak classical characteristics that appear in each well variable. The results of the calculation of the typology of ancient wells are classified into 3 types (Type 1, Type 2 and Type 3). In terms of location, the location of the ancient wells was processed into a two-dimensional map using a Geographic Information System (GIS), to show the spatial distribution in the research area. This approach proves the similarity and continuity of residential areas from the 9th century AD until now. This evidence also confirms that environmental resources in the Prambanan Alluvial Plain, especially groundwater potential, have not experienced significant changes over the period.